Self-Introspection in the Qur'an (A Study of the Thematic Interpretation of the Verses of Muhāsabah Al-Nafs) - Choirul Anwar; Ikhwanudin; Eka Prasetiawati (al-Afkar, Journal For Islamic Studies, 2026)
In the fast-paced digital era, humans are often trapped in worldly routines and distracted by social media, leading to the neglect of their true potential and spiritual values. The concept of muhāsabah al-nafs in the Qur'an offers a solution to this identity crisis, as it emphasizes the importance of self-reflection for moral and spiritual improvement. Although the term is not explicitly mentioned, its values are reflected in verses such as Surah Al-Hashr [59]:18, which urges people to reflect on their deeds. Muhasabah also encompasses social and spiritual dimensions through concepts such as tazkiyah (purification), islah (reformation), tawbah (repentance), sabr (patience), and ihsan (excellence), which encourage inner purification, self-betterment, and positive contributions to society. This study aims to examine Qur'anic verses relevant to muhāsabah al-nafs, analyze their interpretations in classical exegeses such as Al-Iklil, Tarjuman Al-Mustafid, and Al-Maraghi, and relate them to contemporary life contexts, particularly among the younger generation. Using a qualitative approach with the thematic exegesis method (tafsir maudhū‘ī) by Al-Farmawy and literature review, the research reveals that scholars interpret introspection as a key to developing awareness of one’s actions and motivating change toward goodness. A wise person is one who can subdue their desires and work for the hereafter, while the heedless will remain trapped in hypocrisy and loss. This study is expected to enrich the body of knowledge and serve as a practical guide in building spiritual character amidst modern challenges.